Comparative efficacy of different doses of inducing agent on breeding performance of a near threatened catfish pabda (Ompok bimaculatus Bloch, 1794) in West Bengal, India - Samiran Patra; Biswajit Goswami; Tapas Kr. Ghosh; Pujadebi Bera (Journal of Fisheries, 2025)
In India, diversification in shrimp culture area is required due to climate changes, fluctuation in resources, and its marginal profit. Near Threatened pabda (Ompok bimaculatus) may be an alternative aquaculture species which can fulfil all the demands for the shrimp farmers. In this study, healthy, disease-free, 12-month reared brood fishes were collected and stocked in eight tanks (8×4×2 feet) sex wise (130 pairs) with shower facilities. Synthetic hormone was used to induce both male and female fishes at 0.3 and 0.6 ml (T1); 0.5 and 0.7 ml (T2) and 0.7 and 0.8 ml (T3) kg-1 body weight (bw) respectively, having 3 replicates for each treatment. Ovulation period (7 to 11 hours), relative fecundity (105.20±39.93 eggs g–1 bw of female), fertilization rates (67.37±20.73 to 75.88±24.84%), hatching rates (62.57±18.46 to 79.67±26.68%) and survival rates (55.01±14.93 to 65.62±19.91%) were observed. Among treatments, T2 exhibited better breeding performance but no significant differences with other treatments were observed. Important water quality parameters like temperature (28.27±1.68°C), pH (7.10±0.44), dissolved oxygen (4.25±0.37 mg L–1), hardness (210.96±9.31 mg L–1) and alkalinity (202.78±8.00 mg L–1) were also recorded during this experiment. After 48 hours of hatching, hatchlings were reared in aerated tanks for another four days with close observation and fries were harvested 24 days of rearing. From the present experiment, T2 exhibited best effective dose for successful induced breeding of pabda.